2019
DOI: 10.1007/s10853-019-04045-y
|View full text |Cite
|
Sign up to set email alerts
|

Nucleating agents based on graphene and graphene oxide for crystallization of the β-form of isotactic polypropylene

Abstract: During the investigations, functionalization of graphene oxide synthesized using modified Hummers' method and its reduced form was performed. Mixtures of graphene oxide and reduced graphene oxide with pimelic acid and calcium hydroxide were prepared for functionalization. During the reaction, the molecules of pimelic acid were attached to the surface of graphene sheets. By forming links between the carboxylic groups of pimelic acid and graphene oxide, the durable connection was achieved. The functionalized gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 66 publications
2
18
0
Order By: Relevance
“…Due to these bonds, particles of calcium pimelate are attached to the surface of reduced graphene oxide. Formation of permanent bonds was confirmed in previous investigations [35].…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Due to these bonds, particles of calcium pimelate are attached to the surface of reduced graphene oxide. Formation of permanent bonds was confirmed in previous investigations [35].…”
Section: Discussionsupporting
confidence: 84%
“…Due to its specific surface geometry, calcium pimelate is well known as efficient nucleating agent promoting growth of the β-iPP [30]. Previous investigations revealed that calcium pimelate connected with the surface of rGO initiates the growth of the β-form crystals and promotes formation of structure with a considerable amount of the β-iPP [35]. This ability of the rGO-CP is clearly manifested in gravity spun fibers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Graphene oxide was prepared from graphite using a modified Hummers method, and reduced graphene oxide was prepared by the low-temperature thermal reduction. Both procedures were described by the authors in earlier publications [ 29 , 30 ], and details are provided in Supplementary Materials .…”
Section: Methodsmentioning
confidence: 99%